2018
DOI: 10.1002/2211-5463.12457
|View full text |Cite
|
Sign up to set email alerts
|

Anemarrhena asphodeloides Bunge and its constituent timosaponin‐AIII induce cell cycle arrest and apoptosis in pancreatic cancer cells

Abstract: Pancreatic cancer is one of the most recalcitrant and lethal of all cancers. We examined the effects of Anemarrhena asphodeloides ( AA ) and timosaponin‐ AIII ( TAIII ), a steroidal saponin present in AA , on pancreatic cancer cell proliferation and aimed to elucidate their potential apoptotic mechanisms of action. Viability assays and cell cycle analysis revealed that both AA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Moreover, Timo AIII selectively induces cell death in tumor cells but not in normal cells and has been suggested to be a novel potential anticancer compound in recent years [ 14 , 15 ]. Timo AIII presents antitumor activity in various cancers, such as non-small cell lung cancer [ 16 ], pancreatic cancer [ 17 ], melanoma [ 18 , 19 ], breast cancer [ 20 ], hepatocellular carcinoma [ 21 ], colon cancer [ 22 ], promyelocytic leukemia [ 23 ] and so on. In addition, Chen et al found that Timo AIII also reverses multidrug resistance in human chronic myelogenous leukemia [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Timo AIII selectively induces cell death in tumor cells but not in normal cells and has been suggested to be a novel potential anticancer compound in recent years [ 14 , 15 ]. Timo AIII presents antitumor activity in various cancers, such as non-small cell lung cancer [ 16 ], pancreatic cancer [ 17 ], melanoma [ 18 , 19 ], breast cancer [ 20 ], hepatocellular carcinoma [ 21 ], colon cancer [ 22 ], promyelocytic leukemia [ 23 ] and so on. In addition, Chen et al found that Timo AIII also reverses multidrug resistance in human chronic myelogenous leukemia [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these results reveal that TSAIII increases miR-129-5p, which subsequently binds to the 3′-UTR of CTSC gene and suppresses the protein expression of CTSC, and consequently inhibits the migration and invasion of RCC cells. The proposed mechanism that TSAIII inhibits migration and invasion of RCC cells is presented inFigure 8.4 | DISCUSSIONSIt has been reported that TSAIII exerts anticancer activities through various mechanisms, such as induction of apoptosis, autophagy, and cell cycle arrest for BxPC-3, HepG2, and A375-S2 cells(MarElia et al, 2018;Nho, Chun, & Kim, 2016;Wang et al, 2017).Recently, Jung et al, (2016) also reported that TSAIII can inhibit the migration and invasion of A549 cells via ERK/Src/FAK-mediated MMP expression.…”
mentioning
confidence: 99%
“…Thus, mitochondria are at least one of the target structures that suffer from excessive doses and prolonged exposition to A. asphodeloides xanthone fraction. This phenomenon could be also exploited for further anticancer studies as it has been already demonstrated for other constituents from A. asphodeloides rhizoma, i.e., timosaponin A-III and other triterpenoids [34,35].…”
Section: Discussionmentioning
confidence: 69%